Spectrophotometric Determination of Iodine by Oxidation of Dibromo-p-chloro-arsenazo - LI, JING-MEI; ZHAI, QING-ZHOU; WANG, YI (Asian Journal of Chemistry, 2010)
A new method for the determination of iodine by kinetic spectrophotometry was established with the oxidation of dibromo-p-chloroarsenazo (DBC-ASA) by IO3– in presence of KBr. In the medium of 0.30 mol L-1 nitric acid, the maximum absorption peak of IO3– -(DBCASA)- KBr system locates at 510 nm. The absorbance difference (DA) is linearly related with the concentration of IO3– over the range of 0.10- 0.55 μg mL-1. The detection limit of the method was 7.2 ng mL-1. The method was used to determine iodine in kelp, seaweed and dried small shrimps. The relative standard deviation was 1.76-2.09 % for 11 replicate determinations. The recovery of the standard addition was 98.50-102.0 %.